Exploring the influence of innovativeness on the pace of internationalisation of university spin-outs: a born global perspective. Issue 10 (3rd October 2022) - Messina, Lisa; Miller, Kristel; Cunningham, James A.; McAdam, Rodney; Hewitt-Dundas, Nola
ABSTRACT: To date, understanding and empirical investigation of the internationalisation processes of university spin-outs (USOs) have been limited. Few studies have explored the role of the specific characteristics of their core technology, in particular their innovativeness, as a determinant of their early internationalisation. This is also an issue which is under-explored within the general international business field. To address this gap, the purpose of our paper is to examine how the innovativeness of USOs influence the pace of their internationalisation. To achieve this, we explore how innovativeness is nurtured and cumulatively developed during born global (BG) and non-born global (NBG) USOs' pre-foundation technology development trajectory. BGs represent a category of young, usually, high-technology firms that internationalise within 3 years of inception. By exploring the pre-foundation technology development process of Italian USOs across two research-intensive universities, we found that BG and NBG USOs differed in aspects around their innovative proclivity, firm innovativeness and the nature of the innovation. Specifically, we found that BG USOs had a longer pre-foundation period, focused on a specific invention with limited fields of application, and offered 'really new' innovations. BG USOs' products or services were also developed and largely standardised before market entry, which accelerated their internationalisation. In contrast, NBG USOs were characterised by short pre-foundation periods, relied on incremental innovation and a wide spectrum of innovative competencies. They also relied on technologies with a broad scope of market application and customised their offerings based on client needs, which slowed their market entry and internationalisation.